Relasi Agama, Magi Dan Sains Dalam Pentas Politik: Studi Kasus Bunda - Sang Penasehat Spiritual - Hadisaputra - Hadisaputra (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2016)
AbstractModern political institutions that glorifies scientific approaches still open a space formetaphysical ones. In a political competition, science institutionalize itself through politicalsurvey and consultant, and metaphysical aspect ispersonified by spiritual counselors.Thisarticle focuses on the practices of a political spiritual councelor in South Sulawesi, namedBunda. Thesuccessful of Bunda in her practice as a spiritual counselor in the modern eracannot be separated from her ability to to integrate between religion, magi and science. Thisis performed by combining between the aspects of religion and magi, such as zikir ritual (zikirmappateppe’, zikir hajat, and zikir ‘sapu mata’), animal sacrificing, and employing MajelisZikir and orphasn for the zikir; and science aspect can be seen from the zikir package withmeasurable operational costs which can be varied depending on the social status of thecandidate and the number of votes needed.The costs of zikir package vary, and each has itsown consequencewhich is informed to candidate in advance.Key Words: spiritual councelor, candidate, zikir, magi, science, vote, religion.